Sensory-Specific Satiety Dissociates General and Specific Pavlovian-Instrumental Transfer - Lingawi, Nura W.; Berman, Talia; Bounds, Jack; Laurent, Vincent (Frontiers in Behavioral Neuroscience, 2022)
Pavlovian conditioning enables predictive stimuli to control action performance and action selection. The present experiments used sensory-specific satiety to examine the role of outcome value in these two forms of control. Experiment 1 employed a general Pavlovian-instrumental transfer design to show that a stimulus predicting a food outcome energizes performance of an instrumental action earning another food outcome. This energizing effect was removed when the stimulus-predicted outcome, or a novel outcome was devalued by sensory-specific satiety. Experiments 2 and 3 employed a specific Pavlovian-instrumental transfer design to demonstrate that a stimulus predicting a particular food outcome promotes the selection of an instrumental action earning the same, but not a different, food outcome. Remarkably, this effect was maintained when all or just one of the stimulus-predicted outcomes were devalued by sensory-specific satiety. These results indicate that satiety alone removes the expression of general PIT. By contrast, satiety or outcome-specific devaluation do not regulate the expression of specific PIT, which is insensitive to changes in outcome value. This dissociation is consistent with the view that general and specific PIT are two separate phenomena driven by distinct psychological mechanisms.